Institutional determinants of innovations in regional governance in Poland - Wiktorska-Święcka, Aldona; Michalewska-Pawlak, Małgorzata; Klimowicz, Monika (Oficyna Wydawnicza ASPRA, 2017)
The subject of the analysis presented in the book is new, innovative solutions supporting regional development in all their complexity. The monograph presents the results of studies conducted as part of the research project with the view to defining and understanding innovative solutions that have been put in practise in regional governance in Poland; and also to follow the pursuit of strategic objectives of regional development as well as to define the institutional determinants of the implementation of innovative solutions in regional governance. The studies carried out within the framework of the research project “Innovations in regional governance in Poland” was financed by the National Science Centre as part of its research grant no. UMO-2013/09/B/HS5/04522.The book comprises four chapters. In Chapter One, the authors discuss the theoretical aspects of research into innovation in regional governance. The chapter presents the state of research and introduces a conceptualisation of terms essential to the analysis of innovation in regional governance. An important element of the chapter is utilisation the concepts of Europeanisation and multilevel governance in research into innovation processes in regional governance. Chapter Two is devoted to issues concerning the institutional context of regional governance in Poland. The authors present in it the institutional determinants of the regional governance model to be found in Polish regions. In Chapter Three, they discuss definitions and models of innovation in regional governance. The most important part of the chapter is devoted to the presentation of a model for researching innovation in regional governance that provides the basis for verification of the various types of innovation. In Chapter Four, the authors present five case studies of the implementation of innovation in regional governance in Polish institutional practice. The chapter summarizes the research conducted within the framework of the project. The book ends with a conclusion in which the authors present the most important factors facilitating and hampering the creation and implementation of innovation in regional governance in Poland.
Keywords: innovations; regional governance; Europeanization; evaluation; networks; entrepreneurship